Tingkat Kepuasan Petani Terhadap Kualitas Pelayanan Koperasi Lkm-A Puap Subur Di Kabupaten Purbalingga - Meyda Surya, Rosana; Nurdiani, Ulfah; Lutfi Zulkifli (MAHATANI: Jurnal Agribisnis (Agribusiness and Agricultural Economics Journal), 2025)
Member satisfaction with LKM-A services is an indicator of success in improving member welfare. The problem that emerged at the LKM-A PUAP Subur Cooperative was a decrease in the number of members. The aim of this research is to understand the characteristics of respondents, the level of satisfaction, and the factors that farmers prioritize regarding the services provided by cooperatives. The case study method was used to provide detailed and in-depth explanations regarding farmer members of the LKM-A PUAP Subur Cooperative in Purbalingga Regency. The respondents were 45 rice farmers members of the LKM-A PUAP Subur Cooperative using simple random sampling techniques. Data collection took place from May to June 2024. Information was obtained through the interview process, filling out questionnaires, observations and literature studies. Data analysis was carried out using the Customer Satisfaction Index (CSI), Importance Performance Analysis (IPA), and description analysis. This research found that most farmers are men over 60 years old, have a high level of education, and have an average family of 3 to 4 people. The CSI calculation results of 80.30 percent show that farmers are satisfied with cooperative services, but there are several aspects that need to be improved based on IPA calculations, such as holding RATs on time, management can provide clear information, and management always maintains good relationships with members.